Mr. John A Kochevar Chairman E Ainsworth Jr Esq. - KURT L. MALMGREN (Tufts Archival Research Center, 2007)
Collection of after-action reports from several states that just increased cigarette taxes. Provides an overview of the tax situation in each report and highlights important aspects of each regions's tax.